Comparison of experimental and estimated meteor amplitude-time characteristics - Антипов, Иван Евгеньевич; Шернин, Михаил Александрович (Eastern-European Journal of Enterprise Technologies, 2011)
A method for comparing the data of experimental and estimated meteor AТС